Tafsir Education and Religious Moderation in Indonesian Islamic Boarding Schools: A Case Study of Pekanbaru, Riau - Arni, Jani; Chandra, Agus Firdaus; Masyhur, Laila Sari; Naufal, Ichza (Universitas Muhammadiyah Surakarta, 2025)
This study examines the process of instilling the values of religious moderation through learning tafsir in Islamic boarding schools in Pekanbaru City, Riau Province. Departing from the role of Islamic boarding schools as educational institutions as well as centers for character formation, this study highlights that violent acts are still found that show the weak internalization of the value of moderation. Using a qualitative approach, this study found that Qur'anic verses with moderate nuances-such as Surah al-Fatihah (1, 3), al-Baqarah (11–13), al-Furqan (63), Fushilat (34), al-Hujurat (9), and al-Mujadilah (11)-were transmitted through the subject of tafsir. The results of the study show that the internalization of values is carried out through three stages: textual understanding of verses, strengthening values through discussions and case studies, and habituation of behavior in the life of Islamic boarding schools. However, there are variations in implementation between Islamic boarding schools; Some have applied contextual and participatory approaches, while others still use textual lecture methods that lack critical reflection. This study has limitations on limited area coverage and no long-term observations. Nevertheless, these findings provide important implications for the development of a more contextual and effective interpretation pedagogy in building a moderate culture in the Islamic boarding school environment.